Hermit crab bycatch fauna (Decapoda, Anomura) off the coast of Santa Catarina State, Brazil: diversity and spatial-temporal distribution - Stanski, Gilson [UNESP]; Mantelatto, Fernando L.; Leao-Castilho, Antonio [UNESP] (Univ Catolica De Valparaiso, 2016)
Biodiversity and spatial-temporal distribution of hermit crabs captured as bycatch in the nonselective fishery of shrimp were analyzed in this study from July 2010 through June 2011 off coast Santa Catarina State (southern Brazil). Ecological indexes and redundancy analyses were conducted to understand the hermit community and their relationship with environmental factors. In total, 644 specimens were collected, representing two families, five genera, and six species, demonstrating remarkable species richness in the study area, mainly because Santa Catarina is a subtropical region. Isocheles sawayai showed the highest abundance, followed by Loxopagurus loxochelis. Both species demonstrated correlation with temperature (positive) and sediment grain size (negative). The highest richness and evenness values were estimated at the deeper area (17 m). However, in 5 m deep area showed the lowest evenness because of the high dominance of I. sawayai, resulting in a lower estimated diversity. During a period of lower temperature and higher salinity (July), higher levels of diversity were registered, probably because of the lower dominance of tropical species (I. sawayai) and the presence of some species distributed in offshore regions (Petrochirus diogenes, Dardanus insignis and Pagurus exilis). Thus, we detected that the capture effort designated in the shrimp fishery activities had a strong influence in the diversity of hermit crabs and other associated fauna, especially because of catch specimens in expressive abundance at various stages of development, including juveniles. This profile makes us argue in favor of constant monitoring of bycatch resources in order to preserve the marine fauna.
Keywords: hermit crab; habitat selection; fishery; Babitonga Bay; Brasil